2018
DOI: 10.1021/acsami.8b12623
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Surface Coating for Bone Scaffolds Based on the Dark Catalytic Effect of Titanium Dioxide

Abstract: Wiedmer et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 60 publications
(141 reference statements)
0
17
0
Order By: Relevance
“…Therefore, novel solutions and biomaterials are being developed to support tissue regeneration. To date, numerous scaffolds based on ceramics (e.g., titanium dioxide [ 3 , 4 ]), metals [ 5 ], or natural and synthetic polymers [ 6 , 7 ]) have been developed and evaluated in terms of their biocompatibility and bioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, novel solutions and biomaterials are being developed to support tissue regeneration. To date, numerous scaffolds based on ceramics (e.g., titanium dioxide [ 3 , 4 ]), metals [ 5 ], or natural and synthetic polymers [ 6 , 7 ]) have been developed and evaluated in terms of their biocompatibility and bioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 surfaces can be irradiated by visible light or in the absence of light after proper modification, which solves the problems brought by ultraviolet (UV) irradiation like carcinogenic potential [ 7 ]. To shift the band gap of TiO 2 into the visible light region, Nagay et al incorporated nitrogen and bismuth into a TiO 2 coating on Ti implant surfaces.…”
Section: Chemical Treatments With Metallic Agentsmentioning
confidence: 99%
“…Utilizing this phenomenon, Wiedmer et al created sol-gel derived anatase TiO 2 coating on porous ceramic scaffolds and successfully obstructed S. epidermidis biofilm development in the presence of 3% H 2 O 2 . They further found that TiO 2 coatings pretreated with 30% H 2 O 2 could preserve some of the oxidative property even without an oxidative agent [ 7 ].…”
Section: Chemical Treatments With Metallic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the cellular components of tissue engineering, the formation of an artificial tissue requires the presence of a scaffold, which behaves as a template for tissue growth in both the cellular and acellular approaches to tissue engineering. In addition to fulfilling its primary role as a cell carrier and new tissue foundation, scaffolds can also be equipped as pharmaceutical or bio molecule delivery vehicles (e.g., antibacterial [40][41][42][43] or growth factors [44]). As schematically shown in Figure 2, tissue engineering is a multidisciplinary research field founded on three major components: the scaffold, the cells, and growth factors.…”
Section: Figurementioning
confidence: 99%